Stoichiometric Alkane and Aldehyde Hydroxylation Reactions Mediated by In Situ Generated Iron(III)-Iodosylbenzene Adduct - Patrik Török; Dóra Lakk-Bogáth; József Kaizer (Molecules, 2023)
Previously synthesized and spectroscopically characterized mononuclear nonheme, low-spin iron(III)-iodosylbenzene complex bearing a bidentate pyridyl-benzimidazole ligands has been investigated in alkane and aldehyde oxidation reactions. The in situ generated Fe(III) iodosylbenzene intermediate is a reactive oxidant capable of activating the benzylic C-H bond of alkane. Its electrophilic character was confirmed by using substituted benzaldehydes and a modified ligand framework containing electron-donating (Me) substituents. Furthermore, the results of kinetic isotope experiments (KIE) using deuterated substrate indicate that the C-H activation can be interpreted through a tunneling-like HAT mechanism. Based on the results of the kinetic measurements and the relatively high KIE values, we can conclude that the activation of the C-H bond mediated by iron(III)–iodosylbenzene adducts is the rate-determining step.